2019
DOI: 10.1063/1.5120249
|View full text |Cite
|
Sign up to set email alerts
|

Spintronic GdFe/Pt THz emitters

Abstract: We present a spintronic terahertz emitter based on a ferrimagnetic gadolinium-iron alloy (GdxFe1−x) and platinum (Pt). We measure the magnetic-field-dependent terahertz emission of GdxFe1−x/Pt spintronic heterostructures in the entire composition range (0 ≤ x ≤ 1). Excellent agreement is found between the measured data and a theoretical model based on the ratio of in-plane and saturation magnetization, up to a Gd content of x = 0.4 for all applied fields. At a higher Gd content (x ≥ 0.6), the measured terahert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…Similar results were reported by Schneider et al for another RE-TM ferrimagnet, Fe1-xTbx[276]. It was found that a CoGd heterostructure emits a stronger THz compared to the CoTb ones possibly due to a large out-ofplane anisotropy in CoTb[277]. The anomalous Hall effect (AHE) as a possible alternate mechanism of THz generation instead of ISHE has been put forward recently[278].…”
supporting
confidence: 76%
“…Similar results were reported by Schneider et al for another RE-TM ferrimagnet, Fe1-xTbx[276]. It was found that a CoGd heterostructure emits a stronger THz compared to the CoTb ones possibly due to a large out-ofplane anisotropy in CoTb[277]. The anomalous Hall effect (AHE) as a possible alternate mechanism of THz generation instead of ISHE has been put forward recently[278].…”
supporting
confidence: 76%
“…122 This useful property enables the net magnetization, (M A + M B ), of the ferrimagnet to be effectively tuned by changing the temperature of the material, 122 where a temperature change can be induced by exposure to femtosecond laser pulses. 62,127,128 FIM/NM THz emitters based upon Gd x Fe 1 x alloys have been explored 62,122 as they are archetypal rare-earth transition metal ferrimagnets, exhibiting composition and thickness dependent magnetic properties. 129,130 A recent study by Schneider et al 127 has investigated the composition and magnetic field dependent THz emission from Gd x Fe 1 x (20 nm)/Pt (5 nm) heterostructures over the entire composition range (0  x 1).…”
Section: Ferrimagnetic Materialsmentioning
confidence: 99%
“…62,127,128 FIM/NM THz emitters based upon Gd x Fe 1 x alloys have been explored 62,122 as they are archetypal rare-earth transition metal ferrimagnets, exhibiting composition and thickness dependent magnetic properties. 129,130 A recent study by Schneider et al 127 has investigated the composition and magnetic field dependent THz emission from Gd x Fe 1 x (20 nm)/Pt (5 nm) heterostructures over the entire composition range (0  x 1). Figure 17 reveals how the THz emission varies with applied magnetic field strength.…”
Section: Ferrimagnetic Materialsmentioning
confidence: 99%
“…During the last years, THz spintronic emitters have been heavily investigated aiming to obtain large signals and spectral bandwidths and to incorporate them into THz applications ( Papaioannou and Beigang, 2021 ; Bull et al., 2021 ; Wu et al., 2021 ). In particular, a wide range of material properties have been studied including: different material compositions of FM/NM layers with a variety of thicknesses ( Torosyan et al., 2018 ; Seifert et al., 2016 ; Wu et al., 2017 ; Yang et al., 2016 ; Qiu et al., 2018 ), ferrimagnetic/NM structures ( Seifert et al., 2017 ; Schneider et al., 2018 , 2019 ; Fix et al., 2020 ), and antiferromagnetic metal/NM ( Ogasawara et al., 2020 ). In addition, the impact of material interfaces was studied by inserting non-magnetic interlayer material such as Cu,Al, Ti, Au, and ZnO layers in FM/X/NM trilayers ( Gueckstock et al., 2021 ; Papaioannou et al., 2018 ; Seifert et al., 2018 ; Hawecker et al., 2021 ; Li et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%